2014
DOI: 10.15452/cejnm.2014.05.0004
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the incidence of depression in the elderly

Abstract: Depression belongs to the most severe diseases of the elderly people. Quite often, depression is not diagnosed and treated at the older age. Consequently, it leads to deterioration of the overall physical, psychological and social state of an elderly person. Aim: The goal of the quantitative research was to roughly estimate the prevalence of depression among persons who live in houses for the elderly or similar institutions and to find the factors which influence the occurrence of depression. Methods: The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In this sense, death can be viewed as liberation. The negative effect of chronic conditions in the elderly on various aspects of QOL, and on maintenance of self-care in activities of daily living can be found in other studies (Chin, Lee, Lee, 2014;Forjaz et al, 2015), as can the negative effect of poly-morbidity on mobility, occurrence of pain, anxiety and depression Like Kabátová et al (2014), we recorded a high prevalence of depression and anxiety in seniors in this study. The presence of anxiety and depression led to a deterioration in the quality of life in seniors in all domains of the WHOQOL-OLD and WHOQOL-BREF.…”
Section: Discussionsupporting
confidence: 72%
“…In this sense, death can be viewed as liberation. The negative effect of chronic conditions in the elderly on various aspects of QOL, and on maintenance of self-care in activities of daily living can be found in other studies (Chin, Lee, Lee, 2014;Forjaz et al, 2015), as can the negative effect of poly-morbidity on mobility, occurrence of pain, anxiety and depression Like Kabátová et al (2014), we recorded a high prevalence of depression and anxiety in seniors in this study. The presence of anxiety and depression led to a deterioration in the quality of life in seniors in all domains of the WHOQOL-OLD and WHOQOL-BREF.…”
Section: Discussionsupporting
confidence: 72%
“…In our study, we observed that elderly men have a significant prevalence of depression, anxiety, insomnia, and discomfort. Negative affective symptoms, especially the prevalence of depression symptoms, are becoming a major issue as people become older, contributing considerably to a decrease and degradation in elders' quality of life and perhaps being a risk factor for physical problems [10,21,22,23,24]. Our work discusses the issue of the elderly population's quality of life decline, as it has in other nations with varied levels of transition trends and using different approaches [11,29].…”
Section: Discussionmentioning
confidence: 99%
“…= 0.000). Depression affects the quality of life of an individual, as well as the nursing care for a depressed individual [14]. In the overall group of respondents, 46 (86%) said that they feel depressed (always, often).…”
Section: Discussionmentioning
confidence: 99%